2021
DOI: 10.3389/fgene.2021.625985
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Leaf Transcriptome of Chrysanthemum rhombifolium (Ling et C. Shih), a Drought Resistant, Endemic Plant From China

Abstract: Chrysanthemum rhombifolium (Ling et C. Shih), an endemic plant that is extremely well-adapted to harsh environments. However, little is known about its molecular biology of the plant's resistant traits against stress, or even its molecular biology of overall plant. To investigate the molecular biology of C. rhombifolium and mechanism of stress adaptation, we performed transcriptome sequencing of its leaves using an Illumina platform. A total of 130,891 unigenes were obtained, and 97,496 (~74.5%) unigenes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The geographic/ecological conditions, hybridization and polyploidy play important roles in the divergence and speciation of Chrysanthemum . The comparative transcriptome analysis of CM and diploid C. boreale revealed whole-genome duplication (WGD) and gene selection patterns in these taxa ( Won et al, 2017 ); the transcriptomes of C. rhombifolium and C. dichrum were also preliminarily characterized ( Liu et al, 2021a ; Zhang et al, 2021a ), but the phylotranscriptomic analysis covering more Chrysanthemum species has not been reported.…”
Section: Biodiversity and Phylogenetic Relationshipmentioning
confidence: 99%
“…The geographic/ecological conditions, hybridization and polyploidy play important roles in the divergence and speciation of Chrysanthemum . The comparative transcriptome analysis of CM and diploid C. boreale revealed whole-genome duplication (WGD) and gene selection patterns in these taxa ( Won et al, 2017 ); the transcriptomes of C. rhombifolium and C. dichrum were also preliminarily characterized ( Liu et al, 2021a ; Zhang et al, 2021a ), but the phylotranscriptomic analysis covering more Chrysanthemum species has not been reported.…”
Section: Biodiversity and Phylogenetic Relationshipmentioning
confidence: 99%
“…From the transcriptional level, it can be revealed that differential gene expression in plant signal transduction, endogenous hormones, photosynthesis, and other pathways under drought stress will deepen the comprehensive understanding of the mechanism of drought stress resistance (Sprenger et al, 2016). In recent years, an increasing number of studies have used sequencing technology to explore the molecular mechanisms of garden plants under drought stress, such as Salix babylonica and Chrysanthemum rhombifolium, and these results have greatly promoted drought resistance research on garden plants (Xu et al, 2021;Zhang et al, 2021). In research on Pinus massoniana, several transcription factor genes associated with the circadian rhythm (HY5 and LHY), signal transduction (ERF), and defense responses (WRKY) have been identified as playing a key role in adapting to drought stress (Du et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the deep coverage and single base-pair resolution, RNA sequencing (RNA-Seq) is an efficient method to analyze large-scale transcriptome sequence investigations and obtain molecular markers, even in species lacking a reference genome [ 13 , 14 ]. This next-generation sequencing (NGS)-based technique has recently been widely used for d e novo transcriptome sequencing assembly, novel gene and molecular marker discovery, and investigating gene expression in various species [ 15 , 16 , 17 , 18 , 19 ]. Therefore, this study used RNA-Seq and de novo assembly to characterize and annotate the transcriptome of takin muscle, and several unigenes and microsatellite markers were identified.…”
Section: Introductionmentioning
confidence: 99%